Knowledge and practice on the no plastic bag campaign among undergraduate students in Universiti Putra Malaysia (UPM) - Abdullah, Erny Nazlina; Abdul Rahman, Haliza; Mohamed Zain, Izzah Nadhirah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2023)
Introduction: Excessive use of plastic bags causes plastic waste problems. Plastic waste takes a long time to decompose and contributes to serious environmental pollution. The No Plastic Bags campaign is one of the initiatives to tackle this problem. This campaign is important as it raises awareness of the impact of plastic on the environment as well as provides continuous education to the younger generation. This research was carried out to study the knowledge and practice of the ‘No Plastic Bag Campaign’ among undergraduate students at Universiti Putra Malaysia (UPM). Methods: A cross-sectional study was conducted among 380 undergraduate students in UPM obtained through a multistage sampling method consisting of cluster and stratified sampling methods. Modified questionnaires were distributed among the respondents via internet-based platforms which are email and WhatsApp. Data analysis was done using IBM SPSS version 25. Results: The study shows that most of the respondents had a high level of knowledge (97.6) and a moderate level of practice (18.2). However, there was no significant association between knowledge and practice in the No Plastic Bag campaign, as the result shows that (ϰ=4.685, p=0.096). Only the Faculty of Science (ϰ=9.520, p=0.009) showed that there is a significant association between the knowledge and practice regarding the No Plastic Bag campaign. Conclusion: In conclusion, the ‘No Plastic Bags Campaign’ can be used as one of the efforts to tackle plastic waste pollution in Malaysia if the level of practice of the ‘No Plastic Bags Campaign’ among students can be increased.